PENGADAAN PIPA AIR BERSIH UNTUK POSKO PENGUNGSIAN GEMPA CIANJUR DI KAMPUNG CIHERANG - Gaffara, Ghefra Rizkan; Kurniawan, Surya; Nurhaidar, Wa Ode; Kasikoen, Ken Martina; Suwandi, Arief; Rasjidin, Roesfianjah (Nindikayla Institute, 2023)
An earthquake in Cianjur on Monday, November 21, 2022 with a magnitude of 5.6 had a damaging impact, resulting in hundreds of deaths and thousands of buildings being destroyed. Cianjur is one of the areas in West Java that was hit by a disaster this year, and adds to the long list of disasters that will occur in West Java in 2022. The National Disaster Management Agency (BNPB) noted that as of December 29, 2022 there had been 3,507 disasters throughout Indonesia. The total disasters recorded were floods with 1,504 incidents in various regions, followed by 1,042 extreme weather, 633 landslides, 251 land and forest fires, 28 earthquakes, 26 tidal waves, 4 droughts, and one volcanic eruption. The province that experienced the highest number of incidents was West Java, with a total of 819 disasters throughout 2022. Followed by Central Java with 478 disasters, and East Java with 401 disasters. Community service activities from Esa Unggul University were carried out for communities affected by the Cianjur Earthquake in Ciherang Village which were carried out for approximately 3 weeks to help evacuees due to the Cianjur Earthquake.